Biomechanical evaluation of different types of lateral hinge fractures in medial opening wedge high tibial osteotomy. (March 2021) - Chen, Peng; Zhan, Yu; Zhan, Shi; Li, Ruiyang; Luo, Congfeng; Xie, Xuetao
Abstract: Background: Lateral hinge fractures are common complications in the medial opening wedge high tibial osteotomy for treatment of knee osteoarthritis. The rehabilitation protocols are decided depending on the remaining stability following these fractures. This study aimed to evaluate the biomechanical properties of different types of lateral hinge fractures in medial opening wedge high tibial osteotomy. Methods: Twenty synthetic tibia models were used as test samples. A 10-mm bone wedge was removed from the medial side of the proximal tibias to create the bone defect. The samples were then divided into 4 groups: (1) intact lateral hinge; (2) Takeuchi type I fractures; (3) type II fractures; and (4) type III fractures. After fixation with a locking plate, the stability parameters including construct stiffness, wedge displacement, and construct strength were tested under compressive forces and compared among the 4 groups. Findings: No statistical difference was found in the construct stiffness among the 4 groups ( P  = 0.78). The type III fractures had the largest wedge displacement compared with the other 3 groups. The failure loads on average were significantly reduced in the type III fractures compared with those with intact hinge ( P  < 0.01) and in type I fractures ( P  = 0.04). No statistical difference was observed between the type I fractures and the intact hinge in terms of wedge displacement or failure loads. Interpretation: The type III fractures were the most unstable and patients with these fractures should be managed cautiously. Delayed weightbearing and/or additional fixation should be considered. Highlights: The first biomechanical study of lateral hinge fractures in high tibial osteotomy. Takeuchi Type I fractures are the most stable lateral hinge fractures. Takeuchi Type III fractures are the least stable lateral hinge fractures. Additional fixation intraoperatively should be considered in type III fractures. Delayed weightbearing postoperatively is recommended for type III fractures.